If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 2x + 12 Reorder the terms: -4 + 9x = 2x + 12 Reorder the terms: -4 + 9x = 12 + 2x Solving -4 + 9x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 9x + -2x = 12 + 2x + -2x Combine like terms: 9x + -2x = 7x -4 + 7x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 7x = 12 + 0 -4 + 7x = 12 Add '4' to each side of the equation. -4 + 4 + 7x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = 12 + 4 7x = 12 + 4 Combine like terms: 12 + 4 = 16 7x = 16 Divide each side by '7'. x = 2.285714286 Simplifying x = 2.285714286
| 6y*y/6y | | B^2+4b=8 | | 6t^2+24t-100=0 | | 3x^3+4x^2+8x+6= | | 6x+6y=31.78 | | X^2+2x-99999=0 | | 6x+6y=31.95 | | X/5=36/4 | | x=sqrt(9x+63-3) | | 6n+10=19 | | 20x+25y=11700 | | 9(2-3x)-29=8x-(x-23) | | x=0.34x | | 5n+3=21 | | 3/7/8-1/5/8 | | P-11=39 | | 6.2=2.2+r | | 4-4x=5+6x | | 42-r=2 | | (2x)/(9-x^2)0 | | -0.5x+2.26=1.345 | | T+28=51 | | (x-2)(x+2)=32 | | .50/8x | | m-9=-13 | | W^2-11w+30.25=0 | | 9/6n-6 | | 64=4e | | 2x^2+20x+100=98 | | 5*24-3y+3y=36 | | 22+12.5= | | 16=3Y-2 |